(untitled) (Vietnam Journal of Community Medicine, 2024)
Every year, approximately 5.6 million tons of cashew apples have been discarded in the local region of Ia Grai District, Gia Lai Province. In addition to their sugar and mineral content, cashew apples contain biochemical active compounds which confer various health benefits thanks to their antioxidative, anti-inflammatory and anti-cancer properties. Noni fruits, unfortunately, encounter a comparable outcome. Both fruits are currently considered waste products, resulting in large wastage. Objective: The objective of this study is to evaluate the hypoglycemic and anti-proliferative cancer cell effects of a fermented product (NCF) derived from cashew apples and noni fruits. Method: In the study, blood glucose levels were measured using Sivalingam’s (2013) methods and Mosmann’s (1983) method was employed to assess the anti-cancer properties,… Results: The results demonstrated that the NCF contains a substantial amount of antioxidants, which can directly or indirectly contribute to reducing blood glucose levels and inhibit cancer cell growth. Moreover, NCF significantly lowered blood glucose levels in mice and enhanced catalase activity in the mice’s liver (p<0.05). Notably, NCF exhibited significant anticancer effects against liver and cervical cancer (p<0.05). Conclusion: These findings underscore the importance of utilizing overlooked plant by products (Cashew apple and Noni fruits) to develop functional beverages that can potentially contribute to human health protection.